2022
DOI: 10.1590/s1984-29612022043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of coccidiosis in calves from Veracruz, México

Abstract: The objectives of the present study were: (1) to determine the prevalence of Eimeria spp. sporulated oocysts in calves from 26 Municipalities in the Central Zone of the State of Veracruz, Mexico, (2) to identify the Eimeria spp. infecting calves, and (3) to identify the risk factors associated with the presence of Eimeria spp. in tropical cattle. A total of 930 individual fecal samples were analyzed by using the McMaster technique; then, oocysts were maintained in 2.5% potassium dichromate to allow sporulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…In the present investigation, 17.83% overall prevalence of eimeriosis was documented which was somewhat comparable with the previous reports of authors mentioned in references [ 34 , 51 – 53 ] and [ 54 ], who reported 18.5% in Sekela district, 21.1% in and around Gondar area, 22.7% in Dire Dawa, 24.4% in Haramaya, and 22.9% Wolaita Sodo town, respectively. Conversely, it was lower than the previous reports of [ 55 – 59 ] and [ 60 ] who reported an eimeriosis prevalence of 39.7% in Veracruz, México; 32.17% in Punjab, India; 57.2% in Ravi River region, Lahore, Pakistan; 62.5% in Asella Oromia state, Ethiopia; 31.9% in Kombolcha Oromia state, Ethiopia; and 68.1% from Debre Zeit and Addis Ababa, respectively. This disparity in the prevalence of bovine eimeriosis in different regions is likely due to differences in agroecology, study season, and husbandry practices [ 15 , 51 ].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In the present investigation, 17.83% overall prevalence of eimeriosis was documented which was somewhat comparable with the previous reports of authors mentioned in references [ 34 , 51 – 53 ] and [ 54 ], who reported 18.5% in Sekela district, 21.1% in and around Gondar area, 22.7% in Dire Dawa, 24.4% in Haramaya, and 22.9% Wolaita Sodo town, respectively. Conversely, it was lower than the previous reports of [ 55 – 59 ] and [ 60 ] who reported an eimeriosis prevalence of 39.7% in Veracruz, México; 32.17% in Punjab, India; 57.2% in Ravi River region, Lahore, Pakistan; 62.5% in Asella Oromia state, Ethiopia; 31.9% in Kombolcha Oromia state, Ethiopia; and 68.1% from Debre Zeit and Addis Ababa, respectively. This disparity in the prevalence of bovine eimeriosis in different regions is likely due to differences in agroecology, study season, and husbandry practices [ 15 , 51 ].…”
Section: Discussioncontrasting
confidence: 67%
“…On the contrary, another authors [ 5 , 12 , 65 ] documented that E. zuernii and E. bovis were the most pathogenic and mainly associated with clinical coccidiosis in cattle. On the other hand, the authors in reference [ 59 ] reported that Eimeria canadensis was the most prevalent species of coccidia in Veracruz, México.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies found that immunoglobulins obtained from the colostrum were insufficient to prevent coccidiosis caused by Eimeria sp. (Faber et al, 2002;Olivares-Muñoz et al, 2022), the infection rate among Mafriwal calves of less than 1-year-old in this study was lesser than the yearlings.…”
Section: Discussionmentioning
confidence: 46%
“…EM infection occurs more frequently in young animals than in older animals [ 25 ]. Several factors, such as season, climate, and farm sanitation, can also influence the prevalence rate [ 26 ]. The fact that these bulls are mostly raised in individual stalls without grouping may contribute to a lower incidence of EM.…”
Section: Discussionmentioning
confidence: 99%